Features of post-radiation disturbances in the accumulation of calcium ions in intracellular platelet depots at different times of the post-radiation period - Parkhimovich, Olga; Bichan, Olga; Bulanova, Klavdiya (Journal of the Belarusian State University. Ecology, 2023)
Calcium ions are an important intracellular regulator; an increase in their concentration in the cytoplasm plays a key role in determining the functional activity of platelets associated with platelet aggregation and the release reaction. The main way to reduce the concentration of free calcium ions in the platelet cytoplasm is the activation of Ca2+-ATPases of intracellular depositing structures and the plasma membrane, which reduce the cytoplasmic content of calcium due to its reuptake in the depot (resequestration) and the release of Ca2+ from the cell. Platelets express two Ca2+-ATPase isoforms in different depositor structures (SERCA2b and SERCA3) and two plasma membrane Ca2+-ATPase isoforms (PMCA1b and 4b). The SERCA2b isoform, which is Ca2+-ATPase of the dense tubular system, is inhibited by thapsigargin. The SERCA3 isoform present in acidic organelles has low sensitivity to thapsigargin, but high sensitivity to tBHQ (2,5-di-(tert-butyl)-1,4-hydroquinone). When stimulated with micromolar concentrations of thapsigargin and ionomycin, which cause complete depletion of the calcium depots of the tubular system and acid organelles, differences in the levels of accumulated calcium in the norm and in the post-radiation period are found in a calcium-free medium: an increase in calcium concentration by 1.4 times is noted on the 3rd day. In the structures of the tubular system of platelets, under the action of nmolar concentrations of thapsigargin, which inhibit SERCA2b Ca2+-ATPase of tubular systems, a change in the content of deposited calcium in irradiated animals was revealed with an increase on the 3rd day. Under conditions of inhibition of Ca2+-ATPase SERCA3 in a calcium-free medium in platelets on the 3rd day after irradiation at a dose of 1 Gy, a more intense release of calcium ions was also noted compared to the control. On the 10th, 30th, 90th day, there were no statistically significant differences in these indicators. In the calcium-containing medium, a more significant intake of calcium ions from the outside into the cytoplasm was observed due to the activation of depot-controlled mechanisms in the post-radiation period, especially on the 3rd and 10th days.